The Effect Of Tax Digitalization, Social Media, And Hedonism On Msme Compliance - Devina Putri Wardani; Erna Sulistyowati (Universitas Muhammadiyah Tangerang, 2026)
MSME tax compliance in Indonesia remains low despite the sector contributing approximately 60.5% to the national GDP. This indicates that the substantial economic contribution of MSMEs has not been matched by proportional tax compliance. Therefore, this study aims to analyze the effects of tax system digitalization, social media, and hedonism culture on MSME tax compliance in Surabaya. A quantitative causal research design was employed, and primary data were collected through structured questionnaires administered to 100 MSME owners in Surabaya who possessed a Taxpayer Identification Number (NPWP) and actively used digital platforms. Respondents were selected using purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that tax system digitalization and social media have positive and significant effects on tax compliance, while hedonism culture has a negative and significant effect. This study contributes to the application of the Theory of Planned Behavior in the context of digital MSMEs and provides practical implications for the Directorate General of Taxes in designing more targeted tax education strategies.